Digital Resilience Construction in Indonesian Cinema: Victims' Perspective on Gender-Based Online Violence in "Budi Pekerti" (2023) - Chatarina Heny Dwi Surwati; Desas Noel Pitaloka; Monika Sri Yuliarti; Rina Herlina Haryanti; Tri Rejeki Andayani (Jurnal Lingua Idea, 2025)
This paper used the construction of digitally-mediated resilience embedded in culture of Indonesian cinema through a case study of gender-based online violence in “Budi Pekerti” (2023). Using qualitative critical analysis of 16 scenes, the paper showed how the film navigates digital harm and the strategies of digital resilience through the lens of gendered resistance and collective familial response. The paper critically examined the Western-centric model of digital resilience as an individual habitus, and instead studied resilience as a hybrid practice that involves geographically displaced, nurturing ritual and culturally embedded (e.g., Javanese language, food/symbolism). The paper claimed that digitally-mediated resilience for women in Indonesia is embedded in the nation’s collectivist ethos and, hence, in the film resilience was practiced and represented by men and women. As a performance, female characters challenged the digital harm by seeking the truth, correcting in language, and media activism whereas the male characters in the film maintained their reputation. By giving resilience in the film, the paper consequently claimed that institutional systemic barriers and media economy are among the structural conditions that make women’s justice inaccessible in professional space. The film, hence, argued for a culturally-embracing intervention to tackle techno-facilitated violence in the nation’s digital public sphere. By contrasting gendered power and the cultural context, the paper contributes to the media studies’ discourse about digital citizenship, and thereupon offers an insight for policy and community-based intervention regarding the evolving digital public sphere in Indonesia.